Local Cultural Relations and Arabic Language Performance Among Non-Native Speakers Students - Nuroh; Ahmad Sirojudin Abas; Ahmad Habibi Syahid; Zaki Ghufron (Lughawiyyat: Jurnal Pendidikan Bahasa dan Sastra Arab, 2024)
The local culture of Non-Native Speakers students contributes significantly to their performance in using Arabic. Social norms, values and cultural traditions can influence their motivation, perception and learning strategies. The methodology of this study is quantitative using a correlational research design. The purpose of this study is to find out the relationship between local culture and Arabic language performance among Non-Native Speakers students and to find out the aspects of local culture that affect the learning and use of Arabic among Non-Native Speakers students. The data source used in this study is students of the Arabic Language and Literature study program, Sultan Maulana Hasanuddin State Islamic University, Banten. The data collection technique is a questionnaire. Data analysis was carried out using descriptive statistics and quantitative analysis. The results of the research on local culture and Arabic language performance among Non-Native Speakers students are that there is a significant relationship. It can be seen that the r-Calculate value of 0.79 is greater than the r-Table value of 0.51 or the r-Calculate value of > from the r-Table value, then the questionnaire is declared valid. Local cultural aspects that affect the learning and use of Arabic by Non-Native Speakers students are the influence of Islam, local languages and dialects, global and media influences, community support and motivation and perception.